The Effort to Increase Vocabulary Mastery through The Use of Word Cards - Dharlinda Suri; Rozali Rozali; Dian Windriani (IJLHE: International Journal of Language, Humanities, and Education, 2022)
The purpose of this study is to increase students' vocabulary mastery and students' motivation to learn vocabulary in grade I SDN 2 Talang Bandar Lampung. The problem in this study is that whether or not the use of word card media can improve vocabulary mastery and student learning motivation. This study uses a classroom action research method which is done in three cycles. The lesson plan for each cycle is prepared by the teacher. The results of the study can be concluded as follows: first, the increase can be seen from the average score of 58.92 in the first cycle, to 67.5 in the second cycle, and to 86.60 in the third cycle. The increase of the average score that occurred is 19.1%. Second, the increasing of students' ability in mastering the vocabulary is also followed by changes in student learning behavior in a positive direction. Students become happier, active, and give a positive response to vocabulary learning.